2022
DOI: 10.1111/jdv.18327
|View full text |Cite
|
Sign up to set email alerts
|

Facial erythema in patients with atopic dermatitis treated with Dupilumab – a descriptive study of morphology and Aetiology

Abstract: Background The development of dermatitis on face and neck, which was not described in phase 3 clinical trials, has been reported in the literature in patients treated with dupilumab. Little is known regarding the causes or defining features of the facial dermatitis. Objectives We conducted surveys of consecutive patients with AD on dupilumab to describe its clinical features, morphology and aetiology. Methods A multi‐centre prospective cohort study was conducted from 1 January 2020, to 31 December 31 2020. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…AD is a chronic condition that severely affects patients' quality of life (30), and among its various clinical features, HND may be one of the most deleterious symptoms, as the facial skin is involved. Even after the emergence of biologics, including dupilumab, head and neck dermatitis is often encountered in patients with AD (31)(32)(33). Therefore, it is necessary to explore the influence of skin barrier and microbes on the occurrence of HND, in addition to the direct blocking of the Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a chronic condition that severely affects patients' quality of life (30), and among its various clinical features, HND may be one of the most deleterious symptoms, as the facial skin is involved. Even after the emergence of biologics, including dupilumab, head and neck dermatitis is often encountered in patients with AD (31)(32)(33). Therefore, it is necessary to explore the influence of skin barrier and microbes on the occurrence of HND, in addition to the direct blocking of the Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…In studying the medications, the authors conclude that the development of facial erythema may be a result of topical steroid withdrawal. 12 New kinase inhibitors have shown tremendous effects in atopic dermatitis after oral application. A new substance already registered for vitiligo treatment namely ruxolitinib has been used topically in a double-blind placebo-controlled trial in atopic dermatitis.…”
Section: A L L Ergy/ecz E M Amentioning
confidence: 99%
“…This phenomenon was studied in 162 patients with severe atopic dermatitis under Dupilumab treatment; 137 had facial erythema before Dupi treatment, 121 improved, seven got worse and six out of 25 patients developed new facial erythema under Dupilumab. In studying the medications, the authors conclude that the development of facial erythema may be a result of topical steroid withdrawal 12 …”
Section: Allergy/eczemamentioning
confidence: 99%
“…Moreover, transient eosinophilia was also reported, which was evidenced by a significant increase in absolute eosinophil count ( 47 ). Surprisingly, while improvements of pre-existing facial dermatitis, which was suggested to be accociated with the evaluation of Malassezia-specific IgE ( 48 ), was seen after Dupilumab therapy, 24% patients reported new-onset facial erythema after the treatment ( 49 ). Similar pattern could be observed in the trial conducted by Jo et al, with totally 8 worsening cases within 101 patients, and another study carried out by de et al, which demonstrated that erythema, particularly in head and neck areas, was highly expressed after treated by Dupilumab ( 50 , 51 ).…”
Section: Anti-il- 4/13 Antibody Drugsmentioning
confidence: 99%